Stress concentration affecting hydrogen-assisted crack in API X70 pipeline base and weld steel under hydrogen/natural gas mixture. (April 2021) - Nguyen, Thanh Tuan; Heo, Hyeong Min; Park, Jaeyeong; Nahm, Seung Hoon; Beak, Un Bong
Highlights: A relation between stress concentration factor and hydrogen environment embrittlement susceptibility was evaluated. Maximum notched strength were nearly consistent in both base and weld metal as a function of the stress concentration factor. Prominent reduction of the RA only occurred in the base metal with the severity notch. The HEE susceptibility of the base metal was more severe than the results obtained with weld specimens. Abstract: A sudden change in the geometrical parameters of a material, such as bends, T-branches, and welded joints may increase the stress concentration, which in turn may enhance the diffusible hydrogen concentration. In this study, quantitative evaluations of the effect of stress concentration factors on hydrogen environmental embrittlement (HEE) will be studied based on the mechanical performance of notched tensile specimens with variations in the stress concentration factors ( Kt ) of the X70 pipeline base and weld metal. To highlight the role of stress concentration, the tests are performed under a 10 MPa gas mixture condition with a low partial hydrogen pressure. The maximum strengths of the notched specimens were nearly consistent across all Kt values. The degree of HEE susceptibility of the base metal increased with increasing Kt value. However, in the weld metal, prominent reductions in the RA occurred at all Kt values. The complex HEE susceptibility of the weld metal can be attributed to the synergistic action of the microstructure heterogeneity and Kt values.